Florida Solid and Hazardous Waste Regulation Handbook: Federal Legislation - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS, 2004)
This document discusses the important federal laws and regulations that impact solid waste management. Each particular statute is “explained” as it would probably apply to you. It also includes a brief description of the federal agencies responsible for implementing and enforcing these statutes. First and foremost is the Environmental Protection Agency (EPA), but other federal agencies, such as the Department of Agriculture, the U.S. Army Corps of Engineers, and the U.S. Coast Guard, may become involved in the disposal of solid and hazardous wastes. This is EDIS document FE443, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.